Development and Assessment of Traditional and Innovative Media to Reduce Individual HIV/AIDS-Related Stigma Attitudes and Beliefs in India - Catalani, Caricia; Castaneda, Diego; Spielberg, Freya (Frontiers in Public Health, 2013)
Although stigma is considered a major barrier to effective response to the HIV/AIDS epidemic, there is a lack of evidence on effective interventions. This media intervention took place among key HIV-vulnerable communities in Southern India. Two HIV stigma videos were created using techniques from traditional film production and new media digital storytelling. A series of 16 focus group discussions were held in 4 rural and 4 urban sites in South India, with specific groups for sex workers, men who have sex with men, young married women, and others. Focus groups with viewers of the traditional film (8 focus groups, 80 participants) and viewers of the new media production (8 focus groups, 69 participants) revealed the mechanisms through which storyline, characters, and aesthetics influence viewers’ attitudes and beliefs about stigma. A comparative pre-/post-survey showed that audiences of both videos significantly improved their stigma scores. We found that a simple illustrated video, produced on a limited budget by amateurs, and a feature film, produced with an ample budget by professionals, elicited similar responses from audiences and similar positive short-term outcomes on stigma.